Causation: Recurrent Collagenous Colitis Following Repeated Use of NSAIDs - Mohammed Y Al-Ghamdi; Dickran A Malatjalian; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
A case in which a patient who on two occasions developed watery diarrhea and proven collagenous colitis shortly after taking nonsteroidal anti-inflammatory drugs is described. The case report suggests a causal relationship.